2004
DOI: 10.1097/00002030-200401230-00017
|View full text |Cite
|
Sign up to set email alerts
|

Timing of mother-to-child transmission of HIV-1 and infant mortality in the first 6 months of life in Harare, Zimbabwe

Abstract: In the first 6 months of life, IU and IP/ePP transmission contributed more than three-quarters of the 30.7% MTCT. Our data, in addition to serving as a historical comparison, may be useful in designing and evaluating the efficacy of short course antiretroviral trials aimed at reducing MTCT in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 28 publications
4
49
1
2
Order By: Relevance
“…First, a strong concentration of women of peak child- *Weighted average of HIV prevalence at baseline and two rounds of follow-up. HIV prevalence in children estimated from prevalence in pregnant women in the study communities, data on vertical transmission in Zimbabwe (37), and data on postinfection childhood survival (38). † Based on fertility and mortality among uninfected individuals.…”
Section: Discussion Empirical Evidence: Summary and Consistency With mentioning
confidence: 99%
See 1 more Smart Citation
“…First, a strong concentration of women of peak child- *Weighted average of HIV prevalence at baseline and two rounds of follow-up. HIV prevalence in children estimated from prevalence in pregnant women in the study communities, data on vertical transmission in Zimbabwe (37), and data on postinfection childhood survival (38). † Based on fertility and mortality among uninfected individuals.…”
Section: Discussion Empirical Evidence: Summary and Consistency With mentioning
confidence: 99%
“…These periods were calculated for each inter-survey period from data on dates of initial and follow-up household interview and dates of migration into/from household and/or death, where appropriate, and were then aggregated. For infant and early childhood mortality rates, we used indirect estimates derived from data on HIV prevalence in pregnant women (pregnant in the inter-survey periods) collected in the socioeconomic stratum, an estimate of 30.7% for the probability of vertical transmission of HIV infection in Zimbabwe (37), and estimates for age-specific mortality from 0-1 years ( 1 m 0 ) and 1-4 years ( 4 m 1 ) of 0.429 and 0.132 for HIV-infected infants (38) and 0.056 and 0.007 for uninfected infants in sub-Saharan African populations. We assumed that no AIDS deaths occurred in the other age intervals not covered in the individual cohort and estimated non-AIDS mortality for these ages using data from the longitudinal household census adjusted for underreporting (25).…”
Section: Methodsmentioning
confidence: 99%
“…These findings do not encourage the daily administration of vitamin A and beta-carotene to HIV-infected women during pregnancy or lactation. The effects of a single mega dose administered during the early postpartum, as suggested from studies of HIV-uninfected women (Stoltzfus et al, 1993;Roy et al, 1997;Rice et al, 1999;Bahl et al, 2002), are currently being assessed in a randomized clinical trial among HIV-infected women (Zijenah et al, 2004). Direct Effect of vitamin supplementation to HIV-infected pregnant womensupplementation to neonates is one alternative that has proven effective in decreasing child mortality (Humphrey et al, 1996;Rahmathullah et al, 2003); however, it is not known whether vitamin A supplementation to HIV-uninfected infants born to HIV-infected mothers could increase their risk of becoming infected.…”
Section: Discussionmentioning
confidence: 99%
“…Low arm circumference has been validated in epidemiological studies and emergency situations as an indicator of acute wasting (James et al, 1994) and, among HIV-infected African women, it has been identified as an independent predictor of mortality (Lindan et al, 1992) and early MTCT (Zijenah et al, 2004). In a study in Zimbabwe, the mean difference in MUAC between mothers who transmitted HIV to their babies and those who did not was about 9 mm (Zijenah et al, 2004), whereas, we found an average negative zinc effect of 4 mm, limited to the second trimester. Whether this decline is clinically relevant as a predictor of mortality or MTCT is yet to be determined.…”
Section: Zinc Supplements Among Hiv-infected Women E Villamor Et Almentioning
confidence: 99%